The Powers of Dignity : The Black Political Philosophy of Frederick Douglass - Bromell, Nicholas Knowles (Book collections on Project MUSE., 2021)
"Nick Bromell examines how Frederick Douglass forged a distinctively black political philosophy out of his experiences as an enslaved and later nominally free man in ways that challenge Anglo-Continental traditions of political thought."--